Concurrent tolerance allocation for quality with form control using Genetic Algorithm. (21st September 2009) - Ramesh, R.; Jerald, J.
Finding an optimal tolerance for components in an assembly is a vital design function, so that, the products manufactured will have high quality with affordable cost. To get an optimal tolerance value, this paper introduces a new procedure, to allocate tolerances concurrently for both design and manufacturing. To reduce the cost on quality loss, cylindricity, a form control of the geometric tolerance is included. A non-linear multivariable optimisation model formulated by this way is tested for various stack-up conditions on a simple mechanical assembly using genetic algorithm. The results show how form control improves quality and reduces cost. [Received 10 September 2008; Revised 8 December 2008; Accepted 18 April 2009]